(3r+1)(2r-7)=

Simple and best practice solution for (3r+1)(2r-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3r+1)(2r-7)= equation:


Simplifying
(3r + 1)(2r + -7) = 0

Reorder the terms:
(1 + 3r)(2r + -7) = 0

Reorder the terms:
(1 + 3r)(-7 + 2r) = 0

Multiply (1 + 3r) * (-7 + 2r)
(1(-7 + 2r) + 3r * (-7 + 2r)) = 0
((-7 * 1 + 2r * 1) + 3r * (-7 + 2r)) = 0
((-7 + 2r) + 3r * (-7 + 2r)) = 0
(-7 + 2r + (-7 * 3r + 2r * 3r)) = 0
(-7 + 2r + (-21r + 6r2)) = 0

Combine like terms: 2r + -21r = -19r
(-7 + -19r + 6r2) = 0

Solving
-7 + -19r + 6r2 = 0

Solving for variable 'r'.

Factor a trinomial.
(-1 + -3r)(7 + -2r) = 0

Subproblem 1

Set the factor '(-1 + -3r)' equal to zero and attempt to solve: Simplifying -1 + -3r = 0 Solving -1 + -3r = 0 Move all terms containing r to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3r = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3r = 0 + 1 -3r = 0 + 1 Combine like terms: 0 + 1 = 1 -3r = 1 Divide each side by '-3'. r = -0.3333333333 Simplifying r = -0.3333333333

Subproblem 2

Set the factor '(7 + -2r)' equal to zero and attempt to solve: Simplifying 7 + -2r = 0 Solving 7 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2r = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2r = 0 + -7 -2r = 0 + -7 Combine like terms: 0 + -7 = -7 -2r = -7 Divide each side by '-2'. r = 3.5 Simplifying r = 3.5

Solution

r = {-0.3333333333, 3.5}

See similar equations:

| 12a+3B=315 | | (4a+7)(7a^2+8a+4)= | | 6x+30+2=8(2x-5)+22 | | 26-5x=-9 | | 3(x-9)-2x=6x+18 | | 59=4x+7 | | 3z+10=-2z+6 | | logx(3x^2-4x-6)=2 | | 2x+14=7x-6 | | m^2-4m=10 | | 3y-2=18-y | | -x-19=15-3x | | (4x+1)(x-5)= | | .4x+13.5*.6=10 | | 4x^3y^2+8xy-12x^3y=0 | | 121-6x=-55+5x | | 3x-9+2x-3=6x+12-8 | | x(4+5)=5(x-2) | | 3(x+1)+6=-12 | | 121-6x=-55+5 | | 12-2m+5=-5 | | ax+7y=8 | | 3(x+0.1)-4(x-0.5)=5.4 | | -2y-5=y+4 | | 3d-11-7d=5 | | 3(x+0.1)-4(x-0.5)=54 | | 5(m-2)=8(m-2) | | log[2](3x+6)=4 | | 5x(x+5)=0 | | y=(x^2-5)(x^2-x^3) | | x=7i | | 152=-3+5(1+6n) |

Equations solver categories